Knocked Up - Seth Rogan; Seth Rogan; Katherine Heigl; Joanna Kerns; Loudon Wainwright III; Harold Ramis (Universal Studios USA, 2007)
The writer and director of The 40-year-old Virgin delivers another a hilarious hit comedy! They say that opposites attract. Well, for slacker Ben (Seth Rogen) and career girl Alison (Katherine Heigl), that's certainly the case - at least for one intoxicated evening. Two months and several pregnancy tests later, Ben and Alison go through a hysterically funny, anxious and heartwarming journey that leads to huge laughs in the most outrageous comedy of the year!
Language : English Subtitles : No Subtitle
Keywords: Comedy